2010
DOI: 10.1007/s00702-010-0514-4
|View full text |Cite
|
Sign up to set email alerts
|

Early microvascular reactions and blood–spinal cord barrier disruption are instrumental in pathophysiology of spinal cord injury and repair: novel therapeutic strategies including nanowired drug delivery to enhance neuroprotection

Abstract: Spinal cord injury (SCI) is a devastating disease that leads to permanent disability of victims for which no suitable therapeutic intervention has been achieved so far. Thus, exploration of novel therapeutic agents and nano-drug delivery to enhance neuroprotection after SCI is the need of the hour. Previous research on SCI is largely focused to improve neurological manifestations of the disease while ignoring spinal cord pathological changes. Recent studies from our laboratory have shown that pathological reco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 78 publications
(37 citation statements)
references
References 119 publications
0
37
0
Order By: Relevance
“…Endothelial cells, basement membranes, pericytes, and astrocytic end-feet processes constitute a specialized system for this functional barrier [5]. Early microvascular reactions and BSCB disruption are instrumental in the pathophysiology of SCI and repair [6,7].…”
Section: Electronic Supplementary Materialsmentioning
confidence: 99%
“…Endothelial cells, basement membranes, pericytes, and astrocytic end-feet processes constitute a specialized system for this functional barrier [5]. Early microvascular reactions and BSCB disruption are instrumental in the pathophysiology of SCI and repair [6,7].…”
Section: Electronic Supplementary Materialsmentioning
confidence: 99%
“…Previous studies focused largely on alleviating neurological manifestations of the injury while ignoring pathological changes in the spinal cord (3). The compression forces induced by SCI can rupture blood vessels, destroy endothelial cells and pericytes, disrupt the BSCB, and cause production of numerous molecules that result in vascular disruption (4,5).…”
Section: Introductionmentioning
confidence: 99%
“…3 Such rostrocaudal spreading of edema results in further tissue damage and worsened functional outcome. 4 Moreover, a study by Koyanagi et al 5 demonstrated that surgical decompression did not affect cord swelling. Thus, edema following SCI presents as a serious complication, with no effective treatment currently available.…”
Section: Introductionmentioning
confidence: 98%